A violência oculta: um estudo sobre polifarmácia e uso de medicamentos potencialmente inapropriados entre idosos residentes em instituições de longa permanência em Belo Horizonte - Ana Cristina de Azevedo Issa (2022)
Introduction: Population aging brings new demands to health system, particularly those related to long-term care. It is necessary to train health professionals to have an adequate look at the particularities of the elderly, especially the frail, many of whom nursing homes residents. Living in a nursing home (NH) is among the main risk factors for polypharmacy and potentially inappropriate prescriptions, which makes these vulnerable elderly more exposed to adverse health outcomes and consequently hospitalization and death. Objectives: This study aimed to evaluate the presence of polypharmacy and the use of potentially inappropriate medications (PIM) among the elderly population residing in NH in Belo Horizonte, as well as the health problems related to their use. Material and Methods: A cross-sectional observational study was carried out to analyze a sample of 1769 elderly residents in 96 private and public NH in Belo Horizonte. We considered for analysis the presence of polypharmacy and the presence of potentially inappropriate medications according to the explicit (PIME) and implicit (PIMI) criteria. Each of these three conditions were evaluated separately, considering variables that included socio-family profile and the functional clinical profile of each elderly, obtained from the global health assessment, which contained the list of medications in use and the clinical-functional vulnerability index (IVCF-20) of each elderly person, filled in by the institutions’ employees. Results/Discussion: The vast majority of our sample (96.2%) was composed of frail elderly and women (69.3%), with a high prevalence of polypharmacy (58.6%) and inappropriate prescriptions according to explicit (43.2%) and implicit (61%) criteria. The presence of polypharmacy was positively associated with fair/poor self-perception of health, living in a philanthropic NH and with a greater number of residents. The polypharmacy`s prevalence was higher than 50% in the elderly at risk of frailty and frail. Polypharmacy was also associated to impaired cognition and mobility (p<0.005). There was a positive association between PIME and being less than 80 years old, residing in private NH and with less than 20 elderly people, as well as having a health plan. The use of PIME was also associated with hospitalization in the last 6 months (p=0.037). The presence of PIMI was positively associated with female gender, older age, poor health perception and frailty (p<0.001) with a prevalence of almost 80% in very frail elderly. There was an association of PIMI with several negative health outcomes, such as impaired cognition, humor, mobility and recent hospitalizations (p<0.05). Attention is drawn to the high prevalence of anticholinergic and sedative and behavioral drugs, especially antipsychotics. Polypharmacy, inappropriate prescriptions according to explicit and implicit criteria were strongly associated (p<0.05). From these findings, we conclude that lack of knowledge on the complexity of aging and its particularities, without considering their different degrees of dependence and needs, exposes this elderly population, especially the most frail, to different risk situations, being an important cause of iatrogenesis, and therefore, of violence against the elderly.